2017
DOI: 10.1080/14767058.2017.1359830
|View full text |Cite
|
Sign up to set email alerts
|

Negative regulators of Wnt signaling pathway SFRP1 and SFRP3 expression in preterm and term pathologic placentas

Abstract: Our findings indicate the active involvement of negative Wnt regulators SFRP1/SFRP3 in placental development and important role in pathology of pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…WNT1 gene belongs to the WNT signaling pathway, which is involved in cell proliferation, development, and tumor progression. WNT signaling pathway inhibition could contribute to miscarriages and PTB, via decreasing trophoblast proliferation and invasion [42]. Notoriously, WNT2 gene, which is typically overexpressed in placenta, was not DE in our data.…”
Section: Discussionmentioning
confidence: 58%
“…WNT1 gene belongs to the WNT signaling pathway, which is involved in cell proliferation, development, and tumor progression. WNT signaling pathway inhibition could contribute to miscarriages and PTB, via decreasing trophoblast proliferation and invasion [42]. Notoriously, WNT2 gene, which is typically overexpressed in placenta, was not DE in our data.…”
Section: Discussionmentioning
confidence: 58%
“…We have previously shown increased activation of the SFRP family members, inhibitors of the Wnt signaling pathway, in pathological placentas from pregnancies with IUGR [ 9 ]. In addition, it has been found that mice with hypermethylated Wnt2 gene promoter have a lower birth weight (they are small for gestational age, SGA) [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, expression of CTTNBP2 and NSF1 was downregulated in BeWo cells in which HAND1 was knocked down. CTTNBP2 has been shown to have a direct relationship with the WNT signaling pathway (Kelly et al, 2017 ), and downregulation in WNT signaling in the placenta has been associated with pathological pregnancies (Zmijanac Partl et al, 2018 ). Similarly, NFS1 is a gene that has an essential role in iron–sulfur cluster processing making it important for electron transport, enzyme catalysis, and regulation of gene expression as well is iron homeostasis (Brzoska et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%